Implementasi Kebijakan Standarisasi Penghasilan Aparatur Pemerintah Desa di Kabupaten Banyumas - Alfa Mutiara Dewi; Sundarso Sundarso; Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Income Standards Policy for rural government institution in Banyumas Regency refers to Government Regulation No. 43 Year 2014 concerning the Implementation Regulations of Law No. 6 In 2014 about the village. Purpose of establishing the Income Standards Policy for rural government institution is to improve the equity and justice for all the Head of the Village and the Village, and the orderly administration of the village good governance relating to rural finance. Effectiveness of policy implementation is measured using “five right”, ie appropriateness of the policy, the accuracy of the implementation, the target accuracy, precision environment, and the accuracy of the process. In the policy, also used the theory of Edwards III consisting of communication, resources, disposition, and organizational structure, and to identify factors supporting and policy implementation. The results of the study is the emergence of a legal product in the form of Fixed Income, Benefits, and Income Supplement Village Head and the Village in Banyumas as income equalization step for village officials in Banyumas. The author recommends the following suggestions: Open communication pattern between the Government 2 of the village with the Municipality by optimizing net Asmara, Provision of Work Motivation and Discipline of apparatus, and optimize public participation in policy formulation in the area.